2022
DOI: 10.1038/s41598-022-15883-3
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of the cranial form of modern human populations described by analysis of a 3D surface homologous model

Abstract: This study assessed the regional diversity of the human cranial form by using geometric homologous models based on scanned data from 148 ethnic groups worldwide. This method adopted a template-fitting technique for a nonrigid transformation via the iterative closest point algorithm to generate the homologous meshes. Through the application of principal component analysis to 342 sampled homologous models, the largest variation was detected in overall size, and small South Asian crania were clearly verified. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Similarly, if a cross-variable estimate (e.g., Cenac, 2023b) included cranial form dimorphism, then cranial form dimorphism would seem to complement support for southern Africa. However, cranial form is comprised of not only size but also shape (Matsumura et al, 2022), meaning that cranial form dimorphism would be redundant to cranial size and shape dimorphisms when estimating the origin. Given a general indication of a southern origin (Cenac, 2023b), finding the numerically highest coefficients to be in the south for cranial shape dimorphism does add some credence to the expansion being represented, to some level, in cranial shape dimorphism.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, if a cross-variable estimate (e.g., Cenac, 2023b) included cranial form dimorphism, then cranial form dimorphism would seem to complement support for southern Africa. However, cranial form is comprised of not only size but also shape (Matsumura et al, 2022), meaning that cranial form dimorphism would be redundant to cranial size and shape dimorphisms when estimating the origin. Given a general indication of a southern origin (Cenac, 2023b), finding the numerically highest coefficients to be in the south for cranial shape dimorphism does add some credence to the expansion being represented, to some level, in cranial shape dimorphism.…”
Section: Resultsmentioning
confidence: 99%
“…Is an increase in dimorphism with distance from Africa found when the dimorphism is of cranial shape or cranial form? Based on prior research (Cenac, 2022a(Cenac, , 2022b(Cenac, , 2023bHubbe et al, 2009;Kleisner et al, 2021;Matsumura et al, 2022;Messer et al, 2013), the answer might be yes.…”
Section: Cranial Dimorphism: Shape and Formmentioning
confidence: 99%
See 2 more Smart Citations
“…Another potential limitation to the comparison of frontal sinus volumes that have been recorded for different population samples arises from the variation in overall cranial size that may be evident between populations from different parts of the globe. For example, Matsumura et al (2022) assessed regional diversity in cranial form based on skulls from 148 ethnic groups worldwide and observed that the greatest variation detected was in overall size, with the second largest variation being in the length/breadth proportion of the neurocranium. This same caveat pertains to the examination of sexual dimorphism in frontal sinus size, since male and female crania tend to be dimorphic in overall size (e.g., Gonzalez et al, 2011; Toneva et al, 2022) in conjunction with differences in overall body size.…”
Section: Introductionmentioning
confidence: 99%